TANGGUNG JAWAB SOSIAL PERUSAHAAN DALAM MEWUJUDKAN KEADILAN DALAM BISNIS - EP, Apriatni (FORUM, 2011)
Abstract :The role of private enterprise in poverty reduction is still questionable because the company's concern toward social problems is still half-heartedly. Coverage in the media, associated with forest destruction, pollution of river water, as well as other forms of injustice felt by the community is still often heard. This proves the corporate social responsibility in upholding justice in the world of business is still low. Injustices in the economic and social development create a gap, especially in public access to utilize existing resources. On the other hand, companies show their existence in the business world, with their ability to utilize existing resources in the country.Embodiment of business ethics within the context of corporate social responsibility should be accommodated in company policies with the aim to achieve corporate objectives, but do not ignore the social interests of surrounding communities. With good relationship, through the CSR labeled activity, will eventually be able to maintain the existence of the company in the business world.Â Key words: Social Responsibility: Business Ethics; justicepermalink :Â http://ejournal.undip.ac.id/index.php/forum/article/view/3150